Comparison of Ultrasound Scanning and Operative Findings of Undescended Testis in Children - Mostofa, Md Golam; Mahmud, Imtiaz; Mahmud, Md Rayhan (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Undescended testis in male infants, linked to complications like torsion and infertility, now see earlier orchiopexy recommendations, emphasizing the importance of prompt diagnosis and intervention. Objective: To evaluate the presurgical diagnostic accuracy of ultrasonography in the localization and volume of undescended testis in children. Methods: This cross-sectional study was carried out in the Department of Pediatric Surgery, CMH Dhaka and BSH&I, Dhaka, from March 2022 to August 2023. A total of 47 pediatric patients with undescended testis were enrolled in this study. Ultrasonography of both inguinoscrotal regions was done in every sample to see the length, width and location of the testis. Ultrasonography was performed before orchiopexy by experienced radiologist. Statistical analyses of the results were obtained using window-based computer software devised with Statistical Packages for Social Sciences (SPSS v26). Results: There was a significant measure of good agreement with a Kappa Value of 0.806 between the USG position and the per-operative position. Strong positive correlations were found between USG and per-operative lengths (r=0.998; p=0.001), widths (r=0.996; p=0.001) and volumes (r=0.999; p=0.001). Conclusion: Preoperative timed ultrasonography reliably identifies anatomical positions and volumes of undescended testes in children, demonstrating noteworthy diagnostic concordance. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:44-48